2014
DOI: 10.1002/ppap.201400080
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Nosocomial Bacteria IncludingClostridium difficileSpores on Dry Inanimate Surface by Cold Atmospheric Plasma

Abstract: Microbial control is important to prevent nosocomial infections. Cold atmospheric plasma (CAP) is studied as an alternative disinfectant for dry surfaces. Bacterial endospores including Clostridium difficile and vegetative bacteria including Enterococcus faecium are treated on carriers, considering European testing standards. CAP reduces the spore load (106 cfu) by at least 3 log10 as required, independent from the bioburden (≤10 min treatments). Only a 2 log10 reduction is achieved with vegetative bacteria du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Regardless of the specific mode of action, early experimental evidence on microbicidal plasma effects on heat or radiation-sensitive material surfaces spurred further efforts to investigate plasma effects on contaminated or infected tissue. Several in vitro studies on effective inactivation of clinically relevant microorganisms and viruses have produced promising results (51)(52)(53)(54)(55)(56)(57)(58). The first clinical investigations on antiseptic plasma effects on tissue and wounds that followed have shown rather modest microbial reduction rates (59)(60)(61)(62)(63).…”
Section: Biological Plasma Effects and Its Medical Use: Focus On Wounmentioning
confidence: 99%
“…Regardless of the specific mode of action, early experimental evidence on microbicidal plasma effects on heat or radiation-sensitive material surfaces spurred further efforts to investigate plasma effects on contaminated or infected tissue. Several in vitro studies on effective inactivation of clinically relevant microorganisms and viruses have produced promising results (51)(52)(53)(54)(55)(56)(57)(58). The first clinical investigations on antiseptic plasma effects on tissue and wounds that followed have shown rather modest microbial reduction rates (59)(60)(61)(62)(63).…”
Section: Biological Plasma Effects and Its Medical Use: Focus On Wounmentioning
confidence: 99%
“…Previous studies have demonstrated the sporicidal effect of plasma produced in air with surface discharge 30 and a compressed air jet 31 to decontaminate C. difficile spores. The ability of a helium/oxygen atmospheric pressure plasma jet to deactivate C. difficile spores has also been demonstrated 32 , whilst a separate study found helium/oxygen plasma ineffective against C. difficile spores 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A clean dry environment provided the greatest reduction in spores and shortest D value (0.4 minutes), compared to dried albumin (D value = 1.7 minutes) and C. difficile spores suspended in water (D value = 1.8 minutes). The observation that organic matter increases spore survival to plasma exposure has previously been reported by Klampf et al ., 2014, where they assessed a surface micro-discharge against C. difficile endospores in the presence of 0.03% albumin 30 . The presence of organic matter is known to attenuate the efficacy of medical device disinfection 42 and is an important consideration when assessing plasma for high level disinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of 3 log units were achieved for all spore tested, being C. difficile more efficiently inactivated (after 1 min of treatment) than the other spores (both after 2.5 min of treatment). In addition, the authors analyzed the morphology of the examinated spores and no significant changes were observed (Klämpfl and others ). In another study, different strains of C. difficile spores were exposed to cold atmospheric pressure using a mixture of helium and oxygen as a carrier gas.…”
Section: Novel Sterilization Technologiesmentioning
confidence: 99%